Stable Isotope Analysis of Mammalian Enamel From the Early Pleistocene Site of Madigou, Nihewan Basin: Implications for Reconstructing Hominin Paleoenvironmental Adaptations in North China - Xu, Zhe; Pei, Shuwen; Hu, Yaowu; de la Torre, Ignacio; Ma, Dongdong (Frontiers in Earth Science, 2021)
The reconstruction of environmental and climatic changes in the Pleistocene is quite vital for us to understand human evolutionary and behavioral adaptations. Well preserved fluvio-lacustrine sediments at Nihewan basin have yielded rich geological records of Early Pleistocene Paleolithic sites and mammalian fossils which provide a unique opportunity for exploring hominin behavior and paleoecology in North China. While taxonomic studies of mammalian fossils have offered important and indirect clues to the general environmental setting and landscapes of Early Pleistocene humans in the fluvio-lacustrine basin of Nihewan, but direct evidence on the paleoenvironment and paleoclimate is still lack. In this paper, bulk and sequential tooth enamel from several mammal species at the Madigou site (ca. 1.2 Ma) were sampled for stable isotope (C, O) analysis in order to reconstruct the paleoenvironmental and climatic variations. The isotopic results show a varied ecology including grassland and sparse forest landscapes with C3-C4 mixed vegetation dominated and even more C4 vegetation at times. Early humans at Madigou likely experienced cold / warm or dry / wet fluctuations in this northern China basin. We think that the environmental fluctuations and diversified landscapes may have result in the flexibility in various aspects of lithic technological behaviors of early humans, allowing them to face the environmental challenges of northern latitudes after the initial expansion from Africa into East Asia at the onset of the Middle Pleistocene Climate Transition.